2005
DOI: 10.1016/j.ecoenv.2004.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Acid volatile sulfide and simultaneously extracted metals in the sediment cores of the Pearl River Estuary, South China

Abstract: The acid-volatile sulfide (AVS), simultaneously extracted metals (SEM), total metals, and chemical partitioning in the sediment cores of the Pearl River Estuary (PRE) were studied. The concentrations of total metals, AVS, and SEM in the sediment cores were generally low in the river outlet area, increased along the seaward direction, and decreased again at the seaward boundary of the estuary. The amounts of AVS were generally greater in deeper sediments than in surface sediments. SEM/AVS was 41 in the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 35 publications
3
56
3
Order By: Relevance
“…Compared with coastal areas of the other regions, the AVS concentrations in this study were wider than those recorded in Laizhou Bay ), Shen'ao Bay (Du et al 2011), Zhangjiang Estuary, Fujian (Jingchun et al 2010), Pearl River Estuary (Fang et al 2005), Jinzhou Bay (Hansen et al 1996), Futian mangrove, Shenzhen Bay (Chai et al 2015), Huanghe Estuary (Wu et al 2007), north area of the Bohai Bay (Jiang et al 2005), Yangze River Estuary (Sun et al 2009), Mudflat, Zhangjiang Estuary (Jingchun et al 2010), Zhangjiang Estuary (Jingchun et al 2010), and southern East China Sea continental slope (Lin et al 2002). All of these studies did not perform in industrial and high-polluted areas; hence, it is expected to have lower concentration levels of AVS compared with this study that was conducted in heavily industrialized area.…”
Section: Spatial Distribution Of Avs In Sedimentscontrasting
confidence: 56%
See 3 more Smart Citations
“…Compared with coastal areas of the other regions, the AVS concentrations in this study were wider than those recorded in Laizhou Bay ), Shen'ao Bay (Du et al 2011), Zhangjiang Estuary, Fujian (Jingchun et al 2010), Pearl River Estuary (Fang et al 2005), Jinzhou Bay (Hansen et al 1996), Futian mangrove, Shenzhen Bay (Chai et al 2015), Huanghe Estuary (Wu et al 2007), north area of the Bohai Bay (Jiang et al 2005), Yangze River Estuary (Sun et al 2009), Mudflat, Zhangjiang Estuary (Jingchun et al 2010), Zhangjiang Estuary (Jingchun et al 2010), and southern East China Sea continental slope (Lin et al 2002). All of these studies did not perform in industrial and high-polluted areas; hence, it is expected to have lower concentration levels of AVS compared with this study that was conducted in heavily industrialized area.…”
Section: Spatial Distribution Of Avs In Sedimentscontrasting
confidence: 56%
“…Younis et al studied the lagoon Maryut that suffers from almost all possible environmental problems and to quite an extreme degree from various sources, industrial and urban untreated sewage (Qalaa and Umum drains). The findings of SEM were higher than the corresponding values for the sediments in Leizhou Peninsula (Li et al 2014a, b, c), Zhangzi Island, southwestern coastal Laizhou Bay and Laizhou Bay , Shen'ao Bay (Du et al 2011), Zhangjiang Estuary, Fujian (Jingchun et al 2010), Pearl River Estuary (Fang et al 2005), Jinzhou Bay (Hansen et al 1996), Futian mangrove, Shenzhen Bay (Chai et al 2015), Huanghe Estuary (Wu et al 2007), north area of the Bohai Bay (Wu et al 2007), Yangze River Estuary (Sun et al 2009), Mudflat, Zhangjiang Estuary (Jingchun et al 2010), Forest edge (Jingchun et al 2010), Zhangjiang Estuary (Jingchun et al 2010), Forest, Zhangjiang Estuary (Jingchun et al 2010), southern East China Sea continental slope , and Jiaozhou Bay (Huo et al 2001), all in China. The results in the present study were also higher than those recorded in the south coast of São Paulo in Brazil (Nizoli and Luiz-Silva 2012), Douro Estuary in Portugal (Mucha et al 2005), Guadalete River Estuary in Spain (Campana et al 2005), and lagoons (Burullus and Manzalah) in Egypt (Younis et al 2014).…”
Section: Spatial Distribution Of Sem In Sedimentsmentioning
confidence: 66%
See 2 more Smart Citations
“…The concentrations of all the studied metals and AVS were not necessarily significantly correlated with TOC and pH; only the concentration of Cd and [SEM] Pb were significantly correlated with silt and sand (Table 3). These facts suggested that the concentrations of heavy metals and AVS in sediments cannot be simply interpreted by the changes in grain size, pH and TOC concentrations (Fang et al, 2005;Ip et al, 2007;Liu et al, 2007).…”
Section: When the Ratio [Sem]/[avs] Is > 1 Or [Sem]-[avs] > 0 Toximentioning
confidence: 99%